Novel approach to the analysis of fifth-order weakly nonlocal fractional Schrodinger equation with Caputo derivative - Akinyemi, Lanre; Nisar, Kottakkaran Sooppy; Saleel, C. Ahamed; Rezazadeh, Hadi; Veeresha, Pundikala; Khater, Mostafa M. A.; İnç, Mustafa (Elsevier, 2021)
The main goal of this study is to find solutions for the fractional model of the fifth-order weakly nonlocal Schrodinger equation incorporating nonlinearity of the parabolic law and external potential using a recent modification of the homotopy analysis method (HAM) called the q-homotopy analysis transform method (q-HATM). A mixture of q-HAM and Laplace transform is the projected solutions procedure. The method contributes approximate and exact (for some special cases) solutions such as the bright soliton, dark soliton, and exponential solutions. The simulation results using Mathematica package software, demonstrate that only a few terms are enough to achieve precise, effective, and reliable approximate solutions. In addition, in terms of plots for varying fractional order, the physical behavior of q-HATM solutions has been depicted and the numerical simulation is also exhibited. The results of q-HATM reveal that the projected method is competitive, reliable, and powerful for studying complex nonlinear models of fractional type.
Keywords: Weakly nonlocal Schrodinger equation; q-HATM; Parabolic law; Soliton solutions; Laplace transform; Caputo derivative